Reducing the National Stunting Rate, UNRI Kukerta Students Conduct Socialization in Kelurahan Delima, Pekanbaru City - Mayta Novaliza Isda; Nadia Kristina; Diandra Prudentia; Sarah Novita; Qintara Sahira; Fransisca Elvarina; Yana Lisa Warni; Vina Dwi Amanda; Syahrul M.; Fajar Nugraha; M. Rizqy Pratama Syah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The average stunting rate in Indonesia reaches 24.4% in 2021 and the government targets to reduce the stunting rate to 14% by 2024. In order to realize this target, an understanding of stunting is given to the residents of Pekanbaru so that toddlers can be healthy without stunting. The purpose of providing an understanding of stunting is to participate in realizing reducing stunting rates in Indonesia. The method used in realizing this goal is to conduct counselling to the community in the KKN Balek Kampung Delima. The results of the counselling that has been carried out at RW 08 Pomegranate Village Pekanbaru are respondents who listen and provide good responses and reactions during the activity, including filling out questionnaires regarding the counseling carried out, so that the counselling goes well.   Keywords: Stunting, Toddler, Counselling